Non-invasive evaluation of the myocardial substrate of cardiac amyloidosis by gadolinium cardiac magnetic resonance. Issue 3 (6th June 2005) - Perugini, E; Rapezzi, C; Piva, T; Leone, O; Bacchi-Reggiani, L; Riva, L; Salvi, F; Lovato, L; Branzi, A; Fattori, R
Abstract : Objective: To investigate the prevalence and distribution of gadolinium (Gd) enhancement at cardiac magnetic resonance (CMR) imaging in patients with cardiac amyloidosis (CA) and to look for associations with clinical, morphological, and functional features. Patients and design: 21 patients with definitely diagnosed CA (nine with immunoglobulin light chain amyloidosis and 12 transthyretin related) underwent Gd-CMR. Results: Gd enhancement was detected in 16 of 21 (76%) patients. Sixty six of 357 (18%) segments were enhanced, more often at the mid ventricular level. Transmural extension of enhancement within each patient significantly correlated with left ventricular (LV) end systolic volume ( r  =  0.58). The number of enhanced segments correlated with LV end diastolic volume ( r  =  0.76), end systolic volume ( r  =  0.6), and left atrial size ( r  =  0.56). Segments with > 50% extensive transmural enhancement more often were severely hypokinetic or akinetic (p  =  0.001). Patients with > 2 enhanced segments had significantly lower 12 lead QRS voltage and Sokolow-Lyon index. No relation was apparent with any other clinical, morphological, functional, or histological characteristics. Conclusion: Gd enhancement is common but not universally present in CA, probably due to expansion of infiltrated interstitium. The segmental and transmural distribution of the enhancement is highly variable, and mid-ventricular regions are more often involved. Enhancement appears to be associated with impaired segmental and global contractility and a larger atrium.